The Effect of the Traditional Board Game "Dam-Daman" on the Elderly Cognitive Functions at the Elderly Integrated Health Center, Pegongsoran, Pemalang District, Pemalang - Masruroh, Devita Elsa Arum; Isnaini, Nur (Proceedings Series on Health & Medical Sciences, 2022)
The rising number of elderly is due to an increase in life expectancy. However, this can cause a number of illnesses, for example impaired cognitive function. Then, some efforts wear done to maintain cognitive function in the elderly, such as by increasing brain-stimulating avtivities. In particular, the traditional board game of dam-daman is one of the non-pharmacological therapies to inhibit the decline in cognitive function. The objective of this study was to determine the effect of the traditional board game of dam-daman on the cognitive fuction of the elderly at the Elderly Integrated Health Center, Pegongsoran, Pemalang District, Pemalang.This study used a quasi-eksperimental pretest-posttest research design with control group design. The sampling technique of the study was random sampling in which 32 elderly people were selected. In addition, MMSE was employed as the research instrument an Independent Sample T-Test was used to analyze the data.The results showed that the majority of respondents neither went to school and finished elementary school. Most of them did physical activities for daily activities. The MMSE score indicated that the elderly who received the intervention (traditional board game of dam-daman) obtained a significan increase of brain-stimulating activities compared to them who did not.The results of the Independent Sample T-Test test obtained an Asymp.Sig value was 0.000 (P value <0.05). So, there was an effect of the traditional board games of dam-daman on cognitive function in the Elderly Integrated Health Center, Pegongsoran, Pemalang District, Pemalang, in which the Kolmogrov-Smirnov test shows that p value is <0.05.